Pengaruh Variasi Produk dan Promosi Penjualan terhadap Keputusan Pembelian Tachimi Drink - Sherly Nurafni; Citra Savitri; Syifa Pramudita Fadilla (Universitas Kristen Indonesia Toraja, 2026)
Purpose : The purpose of this study is to analyze the effect of product variety and sales promotion on the purchasing decisions of Tachimi Drink consumers in Karawang Regency. This study uses a quantitative approach with a survey method. The study population consists of 450 regular consumers of Tachimi Drink, with a sample size of 82 respondents determined using the Slovin formula and accidental sampling technique. Data were collected through a questionnaire with a Likert scale and analyzed using the Partial Least Square-based Structural Equation Modeling (SEM-PLS) method. Result : The results showed that product variety had a positive and significant effect on Tachimi Drink consumers' purchasing decisions with a path coefficient value of 0.504 and a p-value < 0.05. In addition, sales promotions also had a positive and significant effect on purchasing decisions with a path coefficient value of 0.366 and a p-value < 0.05. Simultaneously, product variety and sales promotions were able to explain 44.6% of purchasing decisions, while the rest was influenced by other variables outside the scope of this study. Conclution : Increasing product variety and implementing effective and consistent sales promotions can encourage an increase in consumer purchasing decisions. Contribution : This research is expected to serve as strategic consideration for Tachimi Drink MSMEs in designing more innovative and sustainable marketing strategies to increase product competitiveness in the local market.